Computational System Biology - Biological systems -- Computer simulation. Systems biology. Computational Biology. View all subjects (Elsevier, 2006)
Computational systems biology is a field that aims to develop a systems level understanding of biological processes using computational techniques. This book presents a compendium of the state-of-the-art in this new era of biological understanding. The contributors review bioinformation engineering and data integration technologies along with biomedical applications. Different computational approaches to model and simulate biological systems are discussed. Current computational research efforts, comprehensively covered in this volume, are focused on regulatory, signaling and metabolic networks. New concepts for computer representations on multi-scales predicting emergent properties of biological systems are introduced.